The effects of mass media on risky sexual behaviors of adolescents in the Philippines - Faraon, Franceska Louise T. (School of Economics, University of the Philippines Diliman, 2019)
This paper examines the relationship of risky sexual behavior outcomes and exposure to mass media, specifically cable and satellite television and the internet, as guided by Harry Triandis_ Model of Interpersonal Behavior or the idea that behaviors are determined by different factors that could be based on the resources available to the people. Using data from the 2015 National Youth Assessment Study, we examine how mass media exposure influences an individual_s engagement in unprotected sex, transactional sex, sex outside relationship, and sex with multiple partners. Other factors affecting risky sexual behavior, such as access to pornographic websites and materials, membership in religious organizations, sexual orientation, educational attainment, living conditions with parents, financial assistance, and age were also explored. Using Ordinary Least Squares (OLS), Logistic, and Probit Regressions, and analyzing marginal effects, comparing across respondents with access to only internet, only traditional media, and both media forms, the results show a positive relationship between exposure to the internet and types of risky sexual behavior. Contrarily, exposure to traditional media, specifically television, has a negative effect on the risky sexual behavior outcomes. Moreover, access to pornographic websites and materials, finishing up to secondary education only, heterosexuality, receiving financial assistance and age are other factors contributing to the likelihood of engaging in risky sexual behaviors. Finally, members of religious organizations and those living with both their parents are less likely to involve in risky sexual activities. Key findings suggest that access and exposure to the internet lead to a high chance of being engaged in risky sexual activities, as opposed to access and exposure to traditional media. Through perceived adverse health outcomes from exposure to mass media, this thesis suggests the need for better media regulation, better sexual and health education, and the need for a genuine reproductive healthcare system in the Philippines.